Implementation of the Comstock Method for Android based Patient Leftovers Food Management - Lu'luil Maknun Sundarina; Mulyani, Sri Hasta; Hiswati, Marselina Endah (International Journal of Informatics and Computation, 2020)
Nowadays, nutritionists should count manually to know how much nutrition they get as the development of technology, social work easier likewise in calculating the patient's food waste so it will be more efficient and not waste much time. This research aims to build an application that can help nutritionists calculate food waste using the Comstock method. The system is designed to use Unified Modeling Language (UML) and programming language Hypertext Preprocessor (PHP) and Hyper Markup Language (HTML). In this paper, we develop a system to enable nutritionists to calculate food waste at the hospital using the Comstock method.